Article Development and Evaluation of BrunerFrame: An EIS-Based Ten-Frame for Improving First-Grade Students' Conceptual Understanding of Subtraction - Sri Utoyo; Bagus Ardi Saputro; Achmad Buchori (Jurnal Pendidikan Terapan, 2026)
Objective: Many first-grade students struggle to develop conceptual understanding of subtraction because mathematics instruction predominantly emphasizes symbolic procedures while providing limited opportunities to connect concrete, visual, and symbolic representations. Although Ten-Frame media are widely used in early mathematics education, few instructional media systematically integrate Bruner's Enactive–Iconic–Symbolic (EIS) representations to facilitate meaningful conceptual learning. Purpose: This study aimed to develop and evaluate the effectiveness of BrunerFrame, an EIS-based Ten-Frame learning media, in enhancing first-grade students' conceptual understanding of subtraction. Methods: This study employed a Research and Development (R&D) approach using the ADDIE model, followed by a quasi-experimental pretest-posttest control group design involving 34 first-grade students from two elementary schools. Data were collected through expert validation, teacher and student response questionnaires, classroom observations, and conceptual understanding tests, then analyzed using descriptive and inferential statistics to examine the validity, practicality, and effectiveness of the developed media. Results: BrunerFrame demonstrated high validity, with material and media validation scores of 88.75% and 90.40%, respectively. Teacher and student practicality scores reached 87.00% and 86.00%, indicating that the media was highly practical for classroom implementation. Students who learned using BrunerFrame achieved significantly higher conceptual understanding than those receiving conventional instruction (p < .001), with a high normalized gain (N-Gain = 0.71) and a very large effect size (Cohen's d = 2.64), demonstrating substantial educational effectiveness. Conclusion: BrunerFrame is a valid, practical, and effective instructional medium that facilitates students' progression from concrete manipulation to visual representation and symbolic reasoning, thereby strengthening conceptual understanding of subtraction. Research Implications: These findings provide empirical evidence supporting the integration of Bruner's EIS theory into elementary mathematics media and offer a practical instructional model for promoting meaningful conceptual learning in primary classrooms. Originality: This study introduces BrunerFrame, a validated instructional medium that systematically integrates Bruner's Enactive, Iconic, and Symbolic representations within a Ten-Frame framework, extending the practical application of EIS theory to early subtraction learning.